Does the occurence of homostyly necessarily accompany the breakdown of heteromorphic incompatibility system? - Zhao, Jing; Kuliku, Laiziti; Zhang, Aiqin; Jiao, Fangfang; Ren, Dengfu (Frontiers in Plant Science, 2025)
IntroductionHeterostyly is a genetic polymorphism that facilitates precise pollen transfer through reciprocal herkogamy. The loss or variation of reciprocal herkogamy is usually accompanied by the breakdown of heteromorphic incompatibility system. Homostyly, which is characterized by self-compatibility and same stigma-anther height is a common floral morph in the variation and evolution of heterostyly. Limonium aureum is a distylous species distributed in the desert of northwest China, in which a floral morph with the same stigma-anther height (H-morph) widely distributed in the natural populations, resembling classical homostyly. The aim of this study was to clarify whether the occurrence of H-morph is also accompanied by the breakdown of heteromorphic incompatibility system, and the relationship between the H-morph and long-styled-/shortstyled-morph (L-/S-morph).MethodsThe floral morphs composition and frequency, heterostylous syndrome, pollinators and visiting efficiency were investigated in five natural populations of L. aureum based on field observation, artificial control pollination experiment and so on.Results and conclusionAll populations were composed of L-, S- and H-morphs, except for ATS population with only H-morph, and there were significant differences in flower size parameter, fruit set, and degree of pollination limitation, while no differences among morphs within population. However, each population demonstrated dimorphic pollen-stigma morphology and a strict heteromorphic incompatibility system, especially ATS population, in which they were compatible between morphs with heteromorphic pollen-stigma morphology, regardless of the reciprocal herkogamy, and vice versa. It is speculated that the H-morph in different populations may be at different stages of heterostylous evolution. The ATS population may be a dimorphic population without reciprocal herkogamy which is in the stage before distyly formation, while the other 4 populations may be dimorphic populations with significant variation in reciprocal herkogamy which is in the stage after distyly formation. The H-morph may be caused by stigma-anther separation shortening of L- and S-morph in other 4 populations. These phenomenons that the variation of floral morph is independent of physiological incompatibility breakdown, as well as the coexistence of populations from different origins and evolutionary stages within the same species have been reported for the first time in the Plumbaginaceae.